2019
DOI: 10.1021/acsami.9b08712
|View full text |Cite
|
Sign up to set email alerts
|

All-Inorganic Flexible Ba0.67Sr0.33TiO3 Thin Films with Excellent Dielectric Properties over a Wide Range of Frequencies

Abstract: With rapid advances in flexible electronics and communication devices, flexible dielectric capacitors exhibiting high permittivity, low loss, and large electric-field tunability over a wide frequency range have attracted increasing attention. Here, a large-scale Ba 0.67 Sr 0.33 TiO 3 (BST) dielectric thin film sandwiched between SrRuO 3 (SRO) bottom electrode and Pt top electrode is fabricated on a flexible mica substrate. The mica/SRO/BST/Pt capacitor exhibits a dielectric constant (ε r ′) of more than 1200, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…While strategies for improved adhesion or clamping via microfabrication may be designed in order to increment the magnitude of the applied strain, [65] our experiment demonstrates the high strain sensitivity of the single-crystal capacitors pre-designed to show large susceptibility at room temperature, with dielectric tunability values comparable to those obtained on Ba 0.5 Sr 0.5 TiO 3 and Ba 0.67 Sr 0.33 TiO 3 films grown on mica for curvatures 5 and 10 times larger, respectively. [11,12] In conclusion, we demonstrate that functionalities in heterostructured oxide nanomembranes can be designed by taking advantage of interlayer elastic interactions. In BaTiO 3 -based nanomembranes, transition temperatures and coercive voltages can be manipulated via structural control and therefore adapted to the desired functionality.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…While strategies for improved adhesion or clamping via microfabrication may be designed in order to increment the magnitude of the applied strain, [65] our experiment demonstrates the high strain sensitivity of the single-crystal capacitors pre-designed to show large susceptibility at room temperature, with dielectric tunability values comparable to those obtained on Ba 0.5 Sr 0.5 TiO 3 and Ba 0.67 Sr 0.33 TiO 3 films grown on mica for curvatures 5 and 10 times larger, respectively. [11,12] In conclusion, we demonstrate that functionalities in heterostructured oxide nanomembranes can be designed by taking advantage of interlayer elastic interactions. In BaTiO 3 -based nanomembranes, transition temperatures and coercive voltages can be manipulated via structural control and therefore adapted to the desired functionality.…”
mentioning
confidence: 67%
“…Even within a single chemistry, multiple phases can be in competition, and their stability can be tuned statically by fixing lattice distortions in epitaxial films or dynamically by applying stress or external fields. Integrating the diverse functionalities of complex oxides into semiconductor [ 1–7 ] and flexible [ 8–12 ] electronics is a major technological challenge that has motivated extensive work. But despite considerable effort, the structural, chemical, and thermal mismatches between such substrates and complex‐oxide materials often yield films with considerably worse crystal quality than that attained on single‐crystal perovskite substrates.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, inorganic flexible mica has become an optimal flexible substrate owing to its superior characteristics of flexibility, high electrical resistance, thermal conductivity, chemically inertia, atomically flat surface, cheapness, and so forth . Recently, flexible ferroelectric materials were realized using mica substrates, including PbZr 0.2 Ti 0.8 O 3 , Ba 0.67 Sr 0.33 TiO 3 , BiFeO 3 (BFO), Bi­(Fe 0.93 Mn 0.05 Ti 0.02 )­O 3 , Hf 0.5 Zr 0.5 O 2 , and so forth. Among the numerous ferroelectric materials being explored, BFO as an environmental-friendly ferroelectric material has been studied extensively on rigid substrates because of its large polarization and exotic multiferroic and photoelectric properties. It has been reported that high ferroelectric remnant polarizations (∼100 μC/cm 2 ) can be achieved in bulk BFO single crystals and epitaxial BFO thin films grown on the rigid substrates in the ground rhombohedral phase along the [111] direction. , In addition to larger polarization, the (111)-oriented BFO film also possesses much more stable polarization under strain compared with the (001) and (110)-oriented BFO films, which should be related to the significant Laudau free energy costs for changing the polarization along the [111] direction. , The stability under strain is very important for flexible electronic applications in terms of the operations under different bending statuses.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds consisting of polar molecules therefore display large dielectric constants in their liquid state and with drastic reduction upon solidification . However, the majority of insulating systems used in practice are solids, which can be broadly classified into three groups, namely organic materials, inorganic materials, and synthetic polymers. Among them, organic dielectric materials possess many attractive features such as higher flexibility, low-cost processing feasibility, smooth surface and low surface energy , compared with the usually employed inorganic and ceramic-based dielectrics, making the former better substitutes. The low surface energy of organic dielectrics results in a cleaner interface and reduced interface traps, causing a reduction in their operating threshold voltages compared with their inorganic counterparts. , Despite all these advantages, one major drawback of organic dielectrics is their very low dielectric constants in comparison to inorganic materials which limits their wider potential applications. , …”
Section: Introductionmentioning
confidence: 99%